An algorithm for the ambulatory monitoring of fetal heart rate - Ibrahimy, Muhammad Ibn; Mohd Ali, Mohd Alauddin; Zahedi, Edmond (2000)
A real-time algorithm has been developed for the simultaneous measurement of the fetal and maternal heart rates from the abdominal signal, which was sampled with 13-bit resolution at 500 Hz. The algorithm is based on digital filtering, adaptive thresholding, differencing of local maxima and minima and statistical properties in the time domain. The technique has been developed through a combination and modification of earlier techniques. The algorithm is found to be effective in resolving the fetal heart rate (FHR) when the fetal R waves and that of the maternal are overlapped. The algorithm has been tested on recorded ambulatory data from 36 to 41 gestational weeks of pregnancy, resulting in an average accuracy of 82% (min, 68%) for the fetal heart rate detection. A microcontroller based system has been developed and the proposed algorithm implemented in real-time. The above system is capable of continuous ambulatory FHR monitoring.